Parent's perception and choice of a good kindergarten school - Mier, Ma. Elena P. (2007)
This survey research study dealt with the factors perceived and considered by parents in their choice of kindergarten school for their children. A survey was conducted to 108 parents from six schools. It was proven that the parents' choice of a kindergarten school is influenced by the physical set up of the school, school provision/facilities, teacher qualifications, teacher qualities, curriculum, approaches, home-school communication, and language of instruction. Curriculum was considered by parents as the most important factor for their choice. Parents, teachers, school administrators, and teacher education institutions have to assume more active roles in the education of kindergarteners.
Thesis (M.A. Teaching in the Early Grades (K-2))--University of the Philippines, Diliman.
Keywords: School choice -- Philippines -- Manila Metropolitan Area; Kindergarten -- Parent participation -- Philippines -- Manila Metropolitan Area